Systematic Reliability Study of Top-Gate p- and n-Channel Organic Field-Effect Transistors - Hwang, Do Kyung; Fuentes-Hernandez, Canek; Fenoll, Mathieu; Yun, Minseong; Park, Jihoon; Shim, Jae Won; Knauer, Keith A.; Dindar, Arnir; Kim, Hyunichul; Kim, Yongjin; Kim, Jungbae; Cheun, Hyeunseok; et al. (American Chemical Society, 2014)
We report on a systematic investigation on the performance and stability of p-channel and n-channel top-gate OFETs, with a CYTOP/Al2O3 bilayer gate dielectric, exposed to controlled dry oxygen and humid atmospheres. Despite the severe conditions of environmental exposure, p-channel and n-channel top-gate OFETs show only minor changes of their performance parameters without undergoing irreversible damage. When correlated with the conditions of environmental exposure, these changes provide new insight into the possible physical mechanisms in the presence of oxygen and water. Photoexcited charge collection spectroscopy experiments provided further evidence of oxygen and water effects on OFETs. Top-gate OFETs also display outstanding durability, even when exposed to oxygen plasma and subsequent immersion in water or operated under aqueous media. These remarkable properties arise as a consequence of the use of relatively air stable organic semiconductors and proper engineering of the OFET structure.